Editorial [Hot Topic: What Have We Learned From Antibiotics? (Guest Editor: James Leif Smith)] - Leif Smith, James (Current Pharmaceutical Biotechnology, 2011)
From a pragmatic perspective, we are all familiar with the clinical need for antibiotics, and many of us understand the role that antibiotics play in maintaining a safe and abundant food supply. However, the study of antibiotics has also contributed to our fundamental understanding of microbial physiology, which has given us wonderful insights into our own physiology. Antimicrobial “mechanisms of action” and antimicrobial resistance studies have furthered our understanding of cell wall synthesis, membrane physiology, cell transport, and other essential enzymatic processes within the microbe. Discovery of antimicrobials has enhanced our understanding of organismal chemistry leading to the discovery of novel enzymes that have potential biotechnological applications for the synthesis of novel compounds. Furthermore, antimicrobials are being utilized in material industrial applications for coating products preventing microbial contamination and biofilm formation in a wide variety of consumer products. Moreover, antimicrobials are now being investigated and utilized for their anticancer and antiviral properties. Antimicrobial research has provided more opportunity for economic growth than any other form of research, while simultaneously providing an enormous amount of knowledge about the world we live in. Although there isn't enough space to touch on all the aspects described above, these reviews do provide the reader with an enormous amount of knowledge and understanding with regard to antimicrobial research and its potential for meeting the challenges ahead. The study of antimicrobial peptides has aided in our understanding of membrane-peptide interactions and membrane physiology. Mohamed Amiche et al. discuss membranotrope activity of antimicrobial peptides, in particular dermaseptins. Futhermore, resistance to antibiotics that target cell wall synthesis is a serious concern for the future treatment of bacterial infections. Marimuthu Jeya et al. discuss efforts that have been made to produce semisynthetic glycopeptides, in particular teicoplanin, with improved pharmacokinetic and pharmacodynamic properties and activity towards resistant strains. These studies provide insight into mechanisms of resistance and cell wall physiology. Bacteriocins from lactic acid bacteria (LAB) and the bacteriocin-producing organisms have been presented by Manuel Montalban- Lopez et al. A wide array of applications ranging from the use of the antibiotic in treating bacterial, fungal, and viral infections to the potential use of the antibiotic producing organism as a probiotic has been presented by the authors. Dr. Kenji Sonomoto's group has presented two reviews on lantibiotics in the area of bioengineering and immunity. Lantibiotics are ribosomally synthesized antibiotics that undergo extensive post translational modifications. Dr. Sonomoto provides a review of the in vitro and in vivo approaches used to produce an active lantibiotic. Furthermore, in the second review, they show that immunity is highly specific to the lantibiotic produced by the lantibiotic producing organism, while methods of immunity vary from pumping to sequestering the lantibiotic. From this review, it is easy to see that the methods for producing lantibiotics as well as the resistance mechanisms of the lantibiotic producing organism are as interesting as the lantibiotic peptide. Given the recent publicized outbreaks of foodborne infections in the United States, food safety has become a serious concern. Min Li et al. offer a review describing natural antimicrobials used in the food industry and their potential for minimizing or eliminating foodborne Staphylococcus aureus (S. aureus) illnesses. A wide array of natural compounds that has significant potential for ensuring a higher level of food safety is described. Their mode of action, bacterial resistance, chemical structure, effectiveness, synergistic effects and future prospects are discussed. In the realm of antifungal research, two reviews are presented. Bing Zhai and Xiaorong Lin present a review in which they describe the potential use of several FDA-approved drugs that were not intended to have antifungal activity for treating fungal infections. In addition, they summarize the mechanism of action and chemical composition of newly discovered antifungal compound and their potential for future therapeutic use. David Tschorner et al. identified more than eighty antifungal peptides in which they have characterized their physiochemical characteristics and activities. Through a structural and functional approach the authors provide a review that may aid in the development of new antimicrobial peptides with improved therapeutic potential. The development of antibiotics has played a major role in increasing our life expectancy and quality of life since the middle of the 20th century. While we do face future challenges in maintaining our advantage over microbial infections and food sustainability, antibiotic research will continue to provide solutions and teach us more about the world we live in.